La « crise » des pâturages dans le Ferlo : une commune tragédie des communs ? - Ronan Mugelé; Olivier Ninot; Néné Dia N’Diaye; Amadou Hamath Diallo (Bulletin de l’Association de Géographes Français)
The lack of pasture space in the Ferlo is nowadays the major concern of herders and various development actors in the sylvopastoral zone. It appears to be the main (re)known symptom, almost habitual, of the cyclical crises affecting pastoralism in Senegal. On the face of it, this situation can be interpreted as a banal ‘tragedy of the commons’, characterised by a significant increase in pressure on the resource, which is itself poorly managed since it belongs to everyone, and whose regeneration is furthermore hampered by both natural (climatic disruption) and anthropogenic (overgrazing, progression of the agricultural front) factors. However, in this situation as in others, the tragedy of the commons is a flawed, even simplistic, interpretative scheme, focusing mainly on the effects of animal demography and community management of grazing land, which are considered to be deleterious. A more detailed analysis of the various factors involved in this "grazing crisis" and the observation of the adaptive strategies of the farmers and the responses proposed by the differents organisations (ngos etc.) supporting the sector (fodder crops, food supplements in particular) lead to the formulation of other hypotheses: the fodder shortage might be the inevitable but underestimated consequence of a long series of interventions in the field of pastoral water supply. Also this crisis might reflect the exhaustion of the entire pastoral breeding model and the beginnings of a profound (and perhaps radical) transformation whose prospects remain uncertain. Rather than a tragedy with an inescapable end, should it not be seen as a turning point for the Ferlo and for pastoralist farming as it exists in the present conditions?